2021
DOI: 10.1029/2020ja028216
|View full text |Cite
|
Sign up to set email alerts
|

Study of Spatiotemporal Development of Global Distribution of Magnetospheric ELF/VLF Waves Using Ground‐Based and Satellite Observations, and RAM‐SCB Simulations, for the March and November 2017 Storms

Abstract: Magnetospheric Extremely Low‐Frequency/Very Low‐Frequency (ELF/VLF) waves have an important role in the acceleration and loss of energetic electrons in the magnetosphere through wave‐particle interaction. It is necessary to understand the spatiotemporal development of magnetospheric ELF/VLF waves to quantitatively estimate this effect of wave‐particle interaction, a global process not yet well understood. We investigated spatiotemporal development of magnetospheric ELF/VLF waves using 6 PWING ground‐based stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Note that the quantitative analysis regarding the global picture of wave contribution is not addressed in this study because it is difficult to derive the spatial distribution of waves only from in‐situ observations. For example, the wave estimation technique based on the distributions of observed precipitating hot electrons detected by NOAA POES satellites (e.g., Chen et al., 2014; Takeshita et al., 2021) would be helpful for the quantitative discussion of the wave contribution. The different time sequences of wave contributions are sometimes observed during other magnetic storms.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the quantitative analysis regarding the global picture of wave contribution is not addressed in this study because it is difficult to derive the spatial distribution of waves only from in‐situ observations. For example, the wave estimation technique based on the distributions of observed precipitating hot electrons detected by NOAA POES satellites (e.g., Chen et al., 2014; Takeshita et al., 2021) would be helpful for the quantitative discussion of the wave contribution. The different time sequences of wave contributions are sometimes observed during other magnetic storms.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that the spatial chorus development is mostly suppressed in the linear growth in the slow solar wind case, but it can still take place the nonlinear growth as exciting dawn chorus in the premidnight-postdawn region in relatively weak geomagnetic activities. Moreover, Takeshita et al (2021) showed a global spatiotemporal development (a longitudinal extent from midnight to morning and dayside associated with substorm electron injections) of the Earth's whistler mode waves given from the linear growth rate using the temperature anisotropy, hot electron density, ambient magnetic field, and cold density by a global simulation. The possible spatial development of chorus generation can be quantitatively estimated by the hot and cold electron densities and ambient magnetic fields (intensity and curvature) from these previous studies based on the linear and nonlinear wave growths.…”
Section: Linear and Nonlinear Wave Growth Ratesmentioning
confidence: 99%